Biochemistry in Contemporary Medicine: Connecting Medicine and Molecules - Shreewastav, Rupesh (Journal of Nobel Medical College, 2025)
Biochemistry, which was once only considered a basic scientific subject in medical curricula, has now become essential to comprehending disease causes, directing diagnostic procedures, and forming therapeutic approaches. The way that biochemistry is currently used in medicine pushes the limits of precision and individualized healthcare by dynamically integrating molecular discoveries with clinical application.